Posicionamentos interacionais e ordens de indexicalidade de sexualidade e gênero de um blogueiro urso - Pereira, Valéria de Rezende (2016)
Living with young students, I realized that, at school, little is said about themes such as sexuality and gender, creating a silence that smothers the pain of those who do not fit the rules of the hegemonic categories. In addition, when the school deals with this topic, it is always from the perspective of reproductive heterosexuality. In this research, I analyze the interactional positionings of sexuality and gender observed in the articles presented on blog Integra, as well as, to identify the indexicality orders of sexuality and gender, perceived in such texts. The blog Integra was created in a heterosexist educational institution, whose context does not cover issues related to the LGBTT group. The theoretical scope uses the concept of performative speech acts developed by Austin ([1962] 1990), Derrida (1988) and Butler (2003), digital literacies proposed by Davies & Merchant (2009) and sexuality and gender concepts by queer theories (BUTLER, 2003; LOURO, 2004). Believing that scientific research must dialogue with the social practices (MOITA LOPES, 2004; RAJAGOPALAN, 2010), I chose the sexuality and gender issues in order to reflect on a theme which is silenced in schools and at the same time quite articulated in web. Furthermore, the work brings out the social subjects of bodies whose stories used to be erase in Modernity. In this sense, I realized a virtual ethnographic research (HINE, 2004) and the data generation instruments are four opinion articles found on the blog. The analytical tools were based on interactional positionings proposed by Goffman ([1979] 1998) and the indexicality orders of Blommaert (2008, 2010). The five indexical clues defined by Wortham (2001), the deictics and modalizations suggested by Bronckart (2007) were used as analysis categories. As a result, I observed that interactional positionings presented in the texts are a blogger blogger from a small town, who claims to be gay and aware of his sexuality. Regarding indexicality orders, I noticed that the blogger points to stratified patterns of meanings regarding norms and socio-cultural conventions over others, such as the country consservatism, the web as a helpful tool to gay relationship and the beautiful physical dictatorship in homoaffective relationships.